An investigation of radial velocities for a horizontal axis wind turbine in axial and yawed flows. (16th April 2012) - Micallef, Daniel; van, Gerard; Ferreira, Carlos Simão; Sant, Tonio
ABSTRACT An experimental and numerical analysis of radial flows in the near wake of a horizontal axis wind turbine is presented for both axial and yawed turbine conditions. Blade performance and wake development are affected because of radial velocities. The phenomenon has not been previously detailed, and current knowledge is limited to the mid to far wake regions. The stereo particle image velocimetry dataset of the model experiments in controlled conditions (MEXICO) rotor is used along with a 3D unsteady potential‐flow panel model. The latter is used, after validation, to give a complete description of the radial velocities and give insight into wake development and geometry. For both axial and yawed flows, the radial velocity is found to increase from root to tip with some complex behaviour in the root and tip regions. For axial flow, radial velocities were found to be appreciable. For yawed flow, because of the in‐plane freestream component, radial velocities are of the scale of the unperturbed flow especially when the blade is in its leeward and windward positions. The implications of this study are particularly relevant for blade element momentum analysis tools that rely on a purely 2D momentum balance approach. Moreover, this study enables further understanding of the wake development process in the proximity of the rotor. Copyright © 2012 John Wiley & Sons, Ltd.